Birth of the Renaissance - Hribar, Maxino Nicora (Masterpieces of Itallian art)
Presents key masterpieces of artistits during the birth of the Renaissance like Alberti, Brunelleechi Luca della Robbia, Donatello, Michelozzo, martini, Giotto, Masaccio.